Mucosal signatures of pathogenic T cells in HLA-B*27+ anterior uveitis and axial spondyloarthritis - Paley, MA; Yang, X; Hassman, LM; Penkava, F; Garner, LI; Paley, GL; Linskey, N; Agnew, R; Arantes de Faria, PH; Feng, A; Li, SY; Simone, D; et al. (American Society for Clinical Investigation, 2024)
HLA-B*27 was one of the first HLA alleles associated with an autoimmune disease, i.e., axial spondyloarthritis (axSpA) and acute anterior uveitis (B27AAU), which cause joint and eye inflammation, respectively. Gastrointestinal inflammation has been suggested as a trigger of axSpA. We recently identified a bacterial peptide (YeiH) that can be presented by HLA-B*27 to expanded public T cell receptors (TCRs) in the joint in axSpA and the eye in B27AAU. While YeiH is present in enteric microbiota and pathogens, additional evidence that pathogenic T cells in HLA-B*27-associated autoimmunity may have had a prior antigenic encounter within the gastrointestinal tract remains lacking. Here, we analyze ocular, synovial, and blood T cells in B27AAU and axSpA, showing that YeiH-specific CD8 T cells express a mucosal gene set and surface proteins consistent with intestinal differentiation, including CD161, integrin α4β7, and CCR6. In addition, we find an expansion of YeiH-specific CD8 T cells in the blood of axSpA and B27AAU over healthy controls, whereas influenza-specific CD8 T cells were equivalent across groups. Lastly, we demonstrate the dispensability of TRBV9 for antigen recognition. Collectively, our data suggest that, in HLA-B27-associated autoimmunity, early antigen exposure and differentiation of pathogenic CD8 T cells may occur in enteric organs.